Developing Reading Skills in Prelingually Deaf Preschool Children: Fingerspelling as a Strategy to Promote Orthographic Learning. (18th May 2021) - Miller, Paul; Banado-Aviran, Efrat; Hetzroni, Orit E
Abstract: The aim of this study was to clarify whether fingerspelling provides a sophisticated mechanism that promotes the development of detailed orthographic knowledge for deaf individuals even in the absence of paralleling phonological knowledge. An intervention program comprised of various procedures chaining between fingerspelled sequences; their written correlates and meaning were administered in a multiple probe single-subject research design across semantic categories to four children with severe to profound prelingual hearing loss (age 4.2–6 years). Results demonstrate the occurrence of rapid orthographic learning during intervention and reliable retention of it in maintenance checks, despite the participants' insufficiently developed phonological skills. Observations of the participants' behavior further suggest fingerspelling to function as an effective mediator in the initial development of robust detailed orthographic lexicon. Analyzes also indicate that "learning through action" and "relevance to the task" provide two key factors in relation to the promotion of orthographic learning, with their absence creating an obvious vacuum in this regard. Insights from the study are discussed with reference to their implication for the development of learning materials and learning environments for prelingually deaf and other novice learners.